Genetic correlation between traits in the ESALQ-PB1 maize population divergently selected for tassel size and ear height Correlação genética entre caracteres na população de milho ESALQ-PB1 após seleção divergente para tamanho do pendão e altura da espiga - Austeclínio Lopes Farias Neto; José Branco de Miranda Filho (Scientia Agricola, 2001)
Full-sib and selfed (S1) progenies were obtained from sub-populations of ESALQ-PB1, divergently selected for tassel size (T+ and T-) and ear height (E+ and E-), and used for estimating genetic and phenotypic correlation coefficients between traits. The analyzed traits were: EW- total ear weight (g/plant), PH- plant height (cm), EH- ear height (cm), TB- tassel branch number and TL- tassel length. The highest genetic (rG) and phenotypic (rF) correlation was observed for the combination PH x EH, as expected, with average of 0.800 and 0.778, respectively over sub-populations and locations. It is apparent that divergent selection for tassel size did not affect greatly the correlation between PH and EH in the full sib progenies, but in the inbred progenies the correlation was smaller in the sub-population selected for larger tassels. Genetic correlation between PH and EH with tassel traits was always positive but ranged from 0.020 to 0.668 in Piracicaba and from 0.06 to 0.309 in Rio Verde. Genetic correlation between PH and EH with yield (EW) also was positive in the range of 0.087 to 0.503. EH showed higher correlation with EW in relation to PH x EW and differences were larger in the sub-populations divergently selected for ear height. Correlation between tassel traits with other traits was positive in most of instances and a lack of consistency was observed among sub-populations. Generally the coefficients of genetic and phenotypic correlation differed substantially from the estimates in the base population ESALQ-PB1 before divergent selection for tassel size and ear placement. Divergent selection affected the correlation between traits under unpredicted and varying magnitudes. Progênies de irmãos germanos e de autofecundação (S1) foram obtidas de sub-populações de ESALQ-PB1 após seleção divergente para tamanho do pendão (T+ e T-) e altura da espiga (E+ e E-) e utilizadas para estimar os coeficientes de correlação genética e fenotípica entre caracteres. Foram analisados os caracteres: EW- peso de espigas (g/planta), PH- altura da planta (cm), EH- altura da espiga (cm), TB- número de ramificações do pendão e TL- comprimento do pendão. Como esperado, as maiores correlações genéticas (rG) e fenotípicas (rF) foram observadas para a combinação PH x EH, com médias de 0,800 e 0,778 , respectivamente, em várias sub-populações e locais. Aparentemente, a seleção divergente para tamanho do pendão não afetou fortemente a correlação entre PH e EH nas progênies de irmãos germanos, mas nas progênies endogâmicas a correlação foi menor na sub-população selecionada para pendão grande. A correlação genética entre PH e EH com os caracteres do pendão foram sempre positivas mas variaram de 0,020 a 0,068 em Piracicaba e de 0,060 a 0,309 em Rio Verde. A correlação genética entre PH e EH com produção (EW) também foi positiva, na faixa de 0,087 a 0,503. EH mostrou maior correlação com EW em relação a PH x EW e as diferenças foram maiores nas sub-populações que sofreram seleção divergente para altura da espiga. A correlação entre os caracteres do pendão com outros caracteres foi positiva na maioria dos casos e uma falta de consistência foi observada entre sub-populações. Em geral, os coeficientes de correlação genética e fenotípica diferiram substancialmente das estimativas na população base ESALQ-PB1 antes da seleção divergente para tamanho do pendão e posição da espiga. A seleção divergente afetou a correlação entre caracteres sob magnitudes imprevisíveis e variáveis.